2021
DOI: 10.3389/fphys.2020.559396
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Autophagy in GAB1-Deficient Vascular Endothelial Cells Is Responsible for Atherosclerosis Progression

Abstract: Autophagy is a host machinery that controls cellular health. Dysfunction of autophagy is responsible for the pathogenesis of many human diseases that include atherosclerosis obliterans (ASO). Physiologically, host autophagy removes aging organelles and delays the formation of atherosclerotic plaque. However, in ischemia event, dysregulated autophagy can be induced to trigger autosis, leading to an inevitable cellular death. Grb2-associated binder 1 (GAB1) is a docking/scaffolding adaptor protein that regulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…The aforementioned studies demonstrated that vascular endothelial cell dysfunction is an important factor leading to AS progression and adverse outcomes. HUVEc cells are often used as the cellular model of AS in previous studies (26)(27)(28). In the present study, OX-LdL induced inflammation and injury, and KLF5 interference inhibited the inflammatory response and improved the function of HUVEcs induced by OX-LdL.…”
Section: Discussionsupporting
confidence: 53%
“…The aforementioned studies demonstrated that vascular endothelial cell dysfunction is an important factor leading to AS progression and adverse outcomes. HUVEc cells are often used as the cellular model of AS in previous studies (26)(27)(28). In the present study, OX-LdL induced inflammation and injury, and KLF5 interference inhibited the inflammatory response and improved the function of HUVEcs induced by OX-LdL.…”
Section: Discussionsupporting
confidence: 53%
“…Qian et al found that excessive autophagy activated by GAB1 deficiency, a docking/scaffolding adaptor protein, inhibited the proliferation of HUVECs lines. 56 Madonna et al reported that excessive autophagy could accelerate myocardial cell death leading to autosis. 57 In addition, excessive autophagy was also found to be able to accelerate the rupture of atherosclerotic plaque in AS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of ERRFI1 190 , ALOX12 191 , SOCS5 192 , DDIT4 193 , DUSP4 194 , IL6ST 195 , DUSP1 196 , SMAD1 197 , NCL (nucleolin) 198 , METTL14 199 , FMOD (fibromodulin) 200 , CYGB (cytoglobin) 201 , UNC5A 202 and TAAR9 203 are believed to be associated with diabetic nephropathy. Genes include FAP (fibroblast activation protein alpha) 204 , EYA4 205 , BCL9 206 , IRF2BP2 207 , EGR3 208 , GADD45B 209 , DMD (dystrophin) 210 , LSR (lipolysis stimulated lipoprotein receptor) 211 , DLL4 212 , SUN2 213 , SOS1 214 , PIK3CA 215 , GAMT (guanidinoacetate N -methyltransferase) 216 , RBM47 217 , HSP90AA1 218 , GAB1 219 , S1PR1 220 , EDNRB (endothelin receptor type B) 221 , NFKBIA (NFKB inhibitor alpha) 222 , GJA1 223 , GADD45G 224 , PHLDA1 225 , CMPK2 226 , FIGN (fidgetin, microtubule severing factor) 227 , KCNJ2 228 , ABCC9 229 , DIRAS3 230 , EPHX1 231 , RAB4A 232 , UBIAD1 233 , CASQ2 234 , TTN (titin) 235 , KCNH1 236 , JPH2 237 , OXGR1 238 , UCHL1 239 , SERPINA3 240 , MMP28 241 , ADAMTS2 242 , P2RY1 243 , CSF2RA 244 , MYO1F …”
Section: Discussionmentioning
confidence: 99%